The power of metacognitive strategies to enhance critical thinking in online learning. - Pereles, Ana; Ortega-Ruipérez, B.; Lázaro, M. (Journal of Technology and Science Education, 2024)
The aim of this study is to verify whether the use of a digital tool, designed to promote the use of metacognitive strategies in self-regulated learning, increases the level of critical thinking during the learning process in trainee teachers in official online master's degrees. The Critical Thinking Questionnaire (CPC 2) was used to assess different dimensions of critical thinking in a sample of 225 students from an online university's master's degree in educational technology. The results showed significant improvements in all dimensions (substantive and dialogic) and associated basic skills (reading, writing, and speaking) for those who used the tool for the promotion of metacognitive strategies. Therefore, it is suggested to work on specific strategies to develop critical thinking as a basis for improving their self-regulated learning.
Keywords: metacognitive strategies; critical thinking; metacognition; self-regulated learning; online learning; online higher education; Scopus